Analisis Semioika Dalam Iklan Politik Gerindra “Sarjana Kerja Kerja Kerja!” - Herman Herman (Al-MUNZIR, 2019)
Gerindra Party's political advertisement, which was viral several weeks ago, caused controversy among netizens. Where the ad was posted on the @Gerindra account on its Twitter page on December 14th. This becomes interesting to study, so that the writer is able to interpret the signs in the ad. The cause of the viral advertisement is the content carried by carrying the icon of the profession "Architecture" which sends many job applications and comes to job interviews, Prapurna (graduate of the predicate Magna Cumlaude Architect) has not yet found a desirable job. Until finally he swerved by trying so many jobs which were not in accordance with his educational background. Starting from the delivery service, bell boy officers, valet parking, to photographers. From this arises the question, How is the representation of Gerindra's political campaign in the "Bachelor of Work Work Work" Advertisement? Can it influence based on the meaning of the signs of the concept of denotation, connotation, and myth in ad text?In order to find answers to the questions above, the author uses Roland Barthes's Semiotic Analysis theory to find signifier, signified, denotative signs, connotative signifier, connotative signified, and connotative signified, and connotative signified connotative signs (connotative signs). This writing is complemented by the meaning of online advertising and its superiority in political campaigns.Keywords: semiotics analysis, advertising, work scholars